A statistical analysis for correlation approach to compensate the measured CIELAB colorimetric data for temperature alterations. Issue 6 (28th May 2017) - Che, Jiangning; Senanayake, Muditha
Abstract: The main focus of this work was to elucidate the further question of whether the color change correlated linearly with the surface temperature alteration or not. We selected and grouped the colored samples, which were in the form of textile, ceramic, plastic, paint, and ink. Those samples were first measured by IR Thermometer to record exact surface temperature, followed by an immediate color measurement using a spectrophotometer. The color variations of these samples were recorded from about 20°C to 60°C. The trend of CIELAB color coordinates was plotted against surface temperature. The dependency between each CIE colorimetric coordinate and the object's surface temperature was statistically evaluated using Pearson's r, R value, and R ‐square analysis. A very strong correlation was observed for ceramic, paint, and ink samples tested, while the textile and plastic sample also exhibited a strong trend. The results added new information about the potential correlation between colorimetric data and temperature. Implications for the future research are discussed.